Literature review: continuous improvement through Lean Six Sigma. (23rd September 2019) - Narottam, Yadav; Mathiyazhagan, K.; Kumar, Krishan
Six Sigma is a business metric used in manufacturing, service and healthcare sectors. The purpose of this paper is to uncovering existing literature gaps in the field of Lean Six Sigma. From the literature review, 2, 461 papers were identified based on publication period of 2003 to 2018. It is concluded from the analysis of the results that no framework available in the literature for successful implementation of LSS. There is a need for empirical study that how to create a continuous improvement culture in the organisation and specific barriers for conducting improvements. Lean Six Sigma can be integrated with other improvement philosophies to achieve overall excellence. The thorough review of existing literature reveals that adoption of LSS plays a vital role in process improvement, variation reduction and defect reduction.